2022
DOI: 10.1002/agm2.12221
|View full text |Cite
|
Sign up to set email alerts
|

Circadian dysfunction and Alzheimer's disease – An updated review

Abstract: Alzheimer's disease (AD) is considered to be the most typical form of dementia that provokes irreversible cognitive impairment. Along with cognitive impairment, circadian rhythm dysfunction is a fundamental factor in aggravating AD. A link among circadian rhythms, sleep, and AD has been well‐documented. The etiopathogenesis of circadian system disruptions and AD serves some general characteristics that also open up the possibility of viewing them as a mutually reliant path. In this review, we have focused on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 147 publications
0
12
0
Order By: Relevance
“…Therefore, it has been confirmed in numerous studies that depression as a neurodegenerative disorder resulting in atrophy of the brain regions 21 . Neurodegenerative disorders develop due to loss of neurons, resulting in a decline in cognitive functioning of the brain 22–28 . Several studies have identified the hippocampus as the key brain region linked to depression, and hippocampal plasticity occurs in patients with depression 29 .…”
Section: Overview On Depressionmentioning
confidence: 96%
“…Therefore, it has been confirmed in numerous studies that depression as a neurodegenerative disorder resulting in atrophy of the brain regions 21 . Neurodegenerative disorders develop due to loss of neurons, resulting in a decline in cognitive functioning of the brain 22–28 . Several studies have identified the hippocampus as the key brain region linked to depression, and hippocampal plasticity occurs in patients with depression 29 .…”
Section: Overview On Depressionmentioning
confidence: 96%
“…259 This is in addition to its ability to inhibit the secretion of soluble APP (amyloid precursor protein) in various cell lines through APP maturation. 262,263 In in vitro and in vivo models, treatment with melatonin decreased amyloid beta production and deposition. [264][265][266][267] Clinical studies are, therefore, needed to explore the potential role of melatonin as a treatment in slowing AD progression and for possible restoration of sleep and circadian rhythms in preclinical AD.…”
Section: Compendium: Circadian Mechanisms In Cardio/ Cerebrovascular ...mentioning
confidence: 99%
“…These individuals also show lower melatonin levels and a dysregulated HPA axis [89]. In fact, circadian dysfunction is a common symptom of AD [90] and a fundamental factor in aggravating the disease [91]. Although impaired circadian rhythms have long been considered a consequence of AD, recent evidence suggests a possible causative role for circadian dysfunction in its pathogenesis.…”
Section: Circadian Disruption In Mental Health Disordersmentioning
confidence: 99%